DIJITALISASI E-COMMERCE WARUNG SAYUR IBU ECIH BERBASIS ANDROID - Iksal Yanuarsyah; Muhammad Risza Purnomo; Nurul Kamilah (JPMUJ, 2024)
Warung Sayur Ibu Ecih, situated in Kp. Kambing RT01/06, Karang Asem Barat, Citeureup, Bogor, is among the food stalls offering a diverse range of vegetables, meats, culinary spices, and more. Customer traffic at the Warung Sayur Ibu Ecih has dwindled due to growing vegetable stalls near Kp. Kambing and the impact of the government-imposed Community Activity Restrictions, which encourage residents to avoid congregating outside their homes. Therefore, a solution is imperative to rekindle buyer interest in the Warung Ibu Ecih and to devise strategies for mitigating shopping crowds. Given this context, the concept of developing an Android-based e-commerce application prototype for the Warung Sayur Ibu Ecih stall has surfaced to lure back customers and circumvent crowding while still adhering to the regulations associated with the government's Community Activity Restrictions. Envisioned as a remedy to attract patrons, this prototype holds the potential to enable convenient vegetable shopping that arises from crowded shopping environments.